Development of school bus security system based on RFID and GSM technologies for Klang Valley Area - Mohamad Fadzir, Tun Mohamad Aqil; Mansor, Hasmah; Gunawan, Teddy Surya; Janin, Zuriati (Institute of Electrical and Electronics Engineers Inc., 2018)
At present, school bus services play a vital role to transport students in every country region from home to schools. Many of parents are relying very much on the school bus services although they are worried about their children safety. Realizing of that problem, this paper proposed a SMS based solution to assist most of parents to identify their kid’s movement (in/out) of the school bus. SMS will be sent to parents once their children ride on the bus and reached the destination. The project aims to develop a school bus security system using RFID and GSM technologies. RFID is used to identify the student’s identity with the parent’s contact number and also head count whereas GSM is used as a platform to notify parent on their kid’s movement via SMS. Tests has been conducted on the overall performance of the developed prototype. From the results, it was found that the developed project is capable to provide a real-time messaging system to parents on their children whereabouts; with an additional feature of student attendance checker. In brief, this developed prototype system could give the peace of mind for most of parents who are entrusting their children traveling with the school bus transportation.